An exploration of the Norwegian academy classification model for talent development in football - Nilsen, A.; Kjærland, G.; Moe, V. F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction Top football is provided with constantly changing requirements, which has led to an increased professionalization of younger players. National plans for payer development have been revised or created to meet these conditions. A major change in Norwegian football came in 2017 with the Academy Classification Model (ACM), a new national plan introduced and developed by the Norwegian Top Football, the interest organization of the clubs in the two top divisions in Norway. The model aims to improve football by developing more quality players within the top clubs. Research on player development is vast; however, few studies include an analysis of national plans. This study aims to explore the ACM documents through a pedagogical lens, and in specific using sports pedagogical models as a framework. Such models consist of special characteristics to ensure learning outcomes. For example, the model must prescribe some specific `non-negotiable` features that make it distinctive. It must leave enough space for local adaption, which is vital to successful sustainable practice, and the content should be based on an explicit knowledge base and values. Research has also pointed at the need for more studies regarding ethics and values within the domain of talent development, which include looking at national documents at the macro-level. The research question illuminated; What are the value and knowledge base of the ACM, the basic characteristics, and the strategies needed to develop talented football players?